2019
DOI: 10.1111/pce.13516
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical changes with needle length are correlated with leaf structural and physiological traits across fivePinusspecies

Abstract: The genus Pinus has wide geographical range and includes species that are the most economically valued among forest trees worldwide. Pine needle length varies greatly among species, but the effects of needle length on anatomy, function, and coordination and trade-offs among traits are poorly understood. We examined variation in leaf morphological, anatomical, mechanical, chemical, and physiological characteristics among five southern pine species: Pinus echinata, Pinus elliottii, Pinus palustris, Pinus taeda, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 78 publications
(103 reference statements)
1
22
1
Order By: Relevance
“…Therefore, it is remarkable that needles form an exception. While the number and diameter of the water‐transporting tracheids in the xylem increase with needle length (Wang et al ., 2006; Zwieniecki et al ., 2006), this is not the case for the phloem SEs, as shown by Rademaker et al . (2017) and here.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is remarkable that needles form an exception. While the number and diameter of the water‐transporting tracheids in the xylem increase with needle length (Wang et al ., 2006; Zwieniecki et al ., 2006), this is not the case for the phloem SEs, as shown by Rademaker et al . (2017) and here.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest a site effect on foliar anatomy, i.e., the ratio of mechanical-tophotosynthetic foliage tissue is altered, where needles with a high DFT (located far from the top of the tree) at the BR site had lower needle density. Wang et al (2019) found that Table 4 Site (S), genotype (G), and density (D) least square means for the non-linear model parameters estimated for the beta model (a sigmoid function) used to describe foliage distribution at absolute and relative scales within the crown. β0, β1, and β2 are the asymptote of foliage in the crown, the point in the crown where the asymptote is achieved and the inflection point at which the increase in leaf area in the crown is maximized, respectively Trees used in this analysis were measured in 2013 and 2017 for crown characteristics at three sites (Virginia, North Carolina, and Brazil) where two genotypes (a clone and an open-pollinated family) of Pinus taeda were planted at 618, 1236, and 1854 tree ha −1 .…”
Section: Leaf Area Distributionmentioning
confidence: 99%
“…Visual shape description in plants is a very specialized and time-consuming task [1, 2]. The botanist and ecologist require straightforward approaches to communicate relevant information about the plant morphology.…”
Section: Introductionmentioning
confidence: 99%